The Transformation of Islamic Education in Indonesia: A Historical Review and Educational Policy: Transformasi Pendidikan Islam Di Indonesia: Tinjauan Historis Dan Kebijakan Pendidikan - Romzi , Moh; Noviyanti, Shobihatul Fitroh; Wahananto , Juri; Fitriani (Transformation of Islamic Management and Education, 2024)
This study aims to analyze the historical development of Islamic education in Indonesia and the policy dynamics that have shaped its transformation from the pre-colonial period to the early post-independence era. The main focus of this research is the role of Islamic educational institutions such as surau, pesantren, and madrasah in forming the religious, social, and intellectual identity of Indonesian Muslim society amid socio-political change. This study employs a qualitative approach using library research methods. Data were collected through a systematic review of relevant academic literature, including scholarly books, peer-reviewed journal articles, historical documents, and policy publications related to Islamic education and educational governance. The collected data were analyzed using a descriptive-qualitative method with a historical perspective to identify patterns of development, continuity, and transformation in Islamic education across different historical phases. The findings indicate that Islamic education in Indonesia has evolved adaptively through continuous interaction between local traditions, religious authority, and state policies. During the colonial period, Islamic education functioned as a form of cultural resistance against discriminatory colonial education systems. In the post-independence period, Islamic education particularly madrasahs experienced increased state recognition through institutional development, curriculum integration between religious and general subjects, and national standardization efforts. This study concludes that Islamic education in Indonesia represents a dynamic and resilient educational system capable of transformation without losing its core religious values. The implications of this research highlight the importance of inclusive, context-sensitive educational policies to strengthen the quality and sustainability of Islamic education in Indonesia.